Comparison of Personality Characteristics and Problem Solving Styles in Addicted and Non-Addicted Men - Mohammad Narimani; Yaghob Habibi; Saeed Rajabi (Drug Control Headquarters, Research and Education Office, 2011)
Introduction: The present study sought to compare emotional intelligence and quality of life in addicted and non-addicted men. Method: The samples included 80 addicted and 80 non-addicted men who addicted men were selected by available sampling and non-addicted men were chosen by cloning methods according to age and marital status. For data collection, emotional intelligence scale and quality of life questionnaire were used. Variance test and Pearson correlation were used for data analysis. Findings: The results showed that there is a significant difference between emotional intelligence and quality of life of addicted and non-addicted men. In fact, the emotional intelligence and quality of life among addicted men were lower than non-addicted men. Also the results showed that there is a significant correlation between emotional intelligence and quality of life among addicts and non addicts. Conclusion: People with low emotional intelligence are more likely to do substance abuse and drug abuse lowers the quality of life of the people. It is likely to develop emotional intelligence of people in order to prevent them from getting addicted.